The Adversity Quotient of the Lecturer Faculty of Nursing, Universitas Padjadjaran in Pandemic COVID-19 - Hanifah, Fathi Dieni; Fitria, Nita; Permana, Ryan Hara; Karisa, Putri (Universitas Pendidikan Indonesia, 2023)
The emergence of various obstacles and challenges during the COVID-19 pandemic can affect the performance of lecturers in carrying out their duties. The dversity quotient is one of the factors that supports one's success in improving one's performance, so measuring the adversity quotient is the first step to discover lecturers' ability to face obstacles and challenges. This study aims to describe the level of adversity quotient for lecturers at the Faculty of Nursing, Universitas Padjadjaran during the COVID-19 pandemic. This study uses a quantitative descriptive method. The subjects studied were 39 nursing faculty lecturers. The instrument used is ARP (Adversity Response Profile) Quick Take TM modified with 40 statement items. The results showed that 23 people (59%) were at the camper-to-climber transition level, two people (5%) were at the camper level, and 14 people (36%) were at the climber level. Based on the sub-dimensions, it is known that the dimensions with the lowest and lowest average values are origin and ownership (37.41) and control (42.53). Lecturers must increase the adversity quotient to help control the challenges they face better. Efforts that can be made are by studying and practicing the LEAD method (Listen, Explore, Analyze, Do). With a good level of adversity quotient, it is hoped that lecturers will be more prepared and maximal in completing assignments, especially related to learning.